Business of the heart : religion and emotion in the nineteenth century - Corrigan, John, 1952- (University of California Press, 2002)
The 'Businessmen's Revival' was a religious revival that unfolded in the wake of the 1857 market crash among white, middle-class Protestants. Delving into the religious history of Boston in the 1850s, John Corrigan gives an imaginative and wide-ranging interpretive study of the revival's significance.